Sobotta Atlas Anatomi Manusia edisi 19 Jilid II : thorax, abdomen, pelvis, ekstremitas bawah - [Tidak Terdaftar] (EGC, 1989)
Sobotta Atlas Anatomi Manusia edisi 19 Jilid II : thorax, abdomen, pelvis, ekstremitas bawa